Injury prevention and rehabilitation for active older adults - Speer, Kevin P. (Human Kinetics, 2005)
With the rise in active participation in sports and exercise by older people, Injury Prevention and Rehabilitation for Active Older Adults is both timely and instructive. It explores the issues involved in working with active older adults, providing a valuable resource to help sports medicine professionals prevent, diagnose, and treat injuries for this growing population.